Uses and abuses of Social Media by Spanish Secondary Education students - Dans-Álvarez-de-Sotomayor, Isabel; Muñoz-Carril, Pablo César; González-Sanmamed, Mercedes (Revista Electrónica Educare, 2022)
Aim. This article focuses on adolescents’ perceptions regarding the use of social media. Specifically, it mainly aims to determine which aspects related to social media are of concern to adolescents from A Coruña (Spain). Method. The study was conducted using a quantitative methodology with a non-experimental design of the ex post facto type and a questionnaire that 1144 adolescents from 4th ESO (Compulsory Secondary Education) answered. Results. The result shows that addiction and deception are the issues of greater concern. Furthermore, there are significant differences between the participants: women are more aware of the risks, and men, with a low academic performance profile, are more daring and feel more conditioned in their mood depending on the social media they use. Conclusions. Young people do know the dangers of social media are reluctant to publicly expose their families, and express different perceptions about their own image and that of their friends.